Detection of Baboon Type C Viral Sequences in Various Primate Tissues by Molecular Hybridization - Benveniste, R. E. (1974)
Nucleic acid sequences homologous to a single-stranded [(3)H]DNA transcript prepared from a baboon type C virus replicating in dog thymus cells can be readily detected in the cellular DNA of several Old World monkeys (baboon, patas, African green, and two species of macaques-rhesus and stumptail). These results demonstrate that primates other than the baboon also contain endogenous type C viral genes. With the hybridization conditions employed (S(1) nuclease, 65 C), no homologous sequences were detected in DNA from human or New World monkey tissues. Of various nonprimate tissues examined, only domestic cat cellular DNA was partially homologous to the baboon virus [(3)H]DNA transcript. In reciprocal experiments, [(3)H]DNA transcripts of RNAs from endogenous cat viruses (RD-114/CCC group) show a significant partial homology with cellular DNA from Old World primates (baboon, patas, and rhesus monkey). The partial homology between type-C-related information in the DNA of domestic cats and various Old World monkeys suggests the possibility of horizontal transmission between the progenitors of these animals at some point in evolution. No nucleic acid sequences homologous to [(3)H]DNA transcripts prepared from type C viruses isolated from tumor tissue of a woolly monkey and a gibbon ape could be detected in any primate tissue DNA examined; however, a partial nucleic acid homology was found between woolly monkey and gibbon ape type C viral [(3)H]DNA and normal mouse cellular DNA.